2021
DOI: 10.1007/s40789-020-00386-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, mineralogy, and thermo-kinetic characterisation of newly discovered Nigerian coals under pyrolysis and combustion conditions

Abstract: In this study, the physicochemical, microstructural, mineralogical, thermal, and kinetic properties of three newly discovered coals from Akunza (AKZ), Ome (OME), and Shiga (SHG) in Nigeria were examined for potential energy recovery. Physicochemical analysis revealed high combustible but low levels of polluting elements. The higher heating values ranged from 18.65 MJ/kg (AKZ) to 26.59 MJ/kg (SHG). Microstructure and mineralogical analyses revealed particles with a rough texture, surface, and glassy lustre, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The first peak of C 6 H 6 generation is usually a result of the degradation and cleavage of coal macromolecular structures. In contrast, the second peak is the product of condensation reactions between aromatic and hydrogenated aromatic structures in coal. , It was reported that with the increase of pyrolysis temperature, the content of monocyclic aromatic hydrocarbons in the tar fraction decreased, while the range of polycyclic aromatic hydrocarbons and their derivatives kept increasing . The heavy-fraction content increased, mainly because the higher pyrolysis temperature caused the dehydrogenation and recondensation of aromatic hydrocarbons in the tar; related scholars found the same pattern in their experiments, and as the final temperature of pyrolysis increased from 550 to 750 °C, the content of benzene substances decreased.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The first peak of C 6 H 6 generation is usually a result of the degradation and cleavage of coal macromolecular structures. In contrast, the second peak is the product of condensation reactions between aromatic and hydrogenated aromatic structures in coal. , It was reported that with the increase of pyrolysis temperature, the content of monocyclic aromatic hydrocarbons in the tar fraction decreased, while the range of polycyclic aromatic hydrocarbons and their derivatives kept increasing . The heavy-fraction content increased, mainly because the higher pyrolysis temperature caused the dehydrogenation and recondensation of aromatic hydrocarbons in the tar; related scholars found the same pattern in their experiments, and as the final temperature of pyrolysis increased from 550 to 750 °C, the content of benzene substances decreased.…”
Section: Resultsmentioning
confidence: 82%
“… 23 , 54 It was reported that with the increase of pyrolysis temperature, the content of monocyclic aromatic hydrocarbons in the tar fraction decreased, while the range of polycyclic aromatic hydrocarbons and their derivatives kept increasing. 55 The heavy-fraction content increased, mainly because the higher pyrolysis temperature caused the dehydrogenation and recondensation of aromatic hydrocarbons in the tar; related scholars found the same pattern in their experiments, and as the final temperature of pyrolysis increased from 550 to 750 °C, the content of benzene substances decreased. Some even disappeared with an increase in temperature, while the naphthalene substances increased with an increase in temperature.…”
Section: Resultsmentioning
confidence: 86%
“… 33 Nyakuma et al through microstructure and mineralogical analyses revealed particles with a rough texture, surface, and glassy luster. 34 These issues should be clarified to reveal the deformation, damage, and failure mechanism of the shaft coal pocket wall. The effective means to investigate these issues was a three-dimensional physical similarity simulation test, which further revealed the deformation, damage, and failure mechanism of the shaft wall.…”
Section: Introductionmentioning
confidence: 99%
“…Hood and Yalcin et al studied about the organic fraction of the coals; Guatame and Rincón analyzed the coal facies changes in the depositional conditions of the sequence in the Eastern Cordillera of Colombia . Nyakuma et al through microstructure and mineralogical analyses revealed particles with a rough texture, surface, and glassy luster . These issues should be clarified to reveal the deformation, damage, and failure mechanism of the shaft coal pocket wall.…”
Section: Introductionmentioning
confidence: 99%